2004
DOI: 10.1021/bi036309n
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Metal Ion Binding in Phosphonoacetaldehyde Hydrolase Identifies Sequence Markers for Metal-Activated Enzymes of the HAD Enzyme Superfamily,

Abstract: The 2-haloalkanoic acid dehalogenase (HAD) family, which contains both carbon and phosphoryl transferases, is one of the largest known enzyme superfamilies. HAD members conserve an R, -core domain that frames the four-loop active-site platform. Each loop contributes one or more catalytic groups, which function in mediating the core chemistry (i.e., group transfer). In this paper, we provide evidence that the number of carboxylate residues on loop 4 and their positions (stations) on the loop are determinants, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 28 publications
1
39
0
Order By: Relevance
“…Several of the conserved residues in motifs I and III of many HAD superfamily proteins are involved in the coordination shell of a divalent metal ion cofactor (Zhang et al, 2004). In the active site of the open conformation of the SPP structure, we observed a high electron density that we interpret to be a Mg 2þ ion, given the enzyme's dependence on Mg 2þ for catalytic activity and its high affinity for this metal ion (the activation constant is 70 mM; Lunn, 2002).…”
Section: The Metal Ionmentioning
confidence: 83%
See 2 more Smart Citations
“…Several of the conserved residues in motifs I and III of many HAD superfamily proteins are involved in the coordination shell of a divalent metal ion cofactor (Zhang et al, 2004). In the active site of the open conformation of the SPP structure, we observed a high electron density that we interpret to be a Mg 2þ ion, given the enzyme's dependence on Mg 2þ for catalytic activity and its high affinity for this metal ion (the activation constant is 70 mM; Lunn, 2002).…”
Section: The Metal Ionmentioning
confidence: 83%
“…Presumably, the negatively charged phosphate group of Suc6P would attract the Mg 2þ ion, and substrate binding might also indirectly favor movement of the Mg 2þ ion into the catalytic position by inducing conformational changes in the active site. The altered position of the Mg 2þ ion in the D12A mutant of the Bacillus cereus phosphonatase suggests that the nucleophilic Asp residue has a strong influence on the position of the metal ion (Zhang et al, 2004). In the crystals of SPP soaked with Suc6P ( Figure 4C), we observed only sucrose and phosphate bound at the active site, indicating that the Suc6P had been completely dephosphorylated.…”
Section: Role Of the Metal Ion In Substrate Bindingmentioning
confidence: 89%
See 1 more Smart Citation
“…This suggests that these proteins use different catalytic mechanisms to catalyze the same reaction. The molecular mechanisms of this catalytic reaction have been characterized only for HAD-like phosphohydrolases (36,37), which cleave covalent bonds of phosphorylated substrates by nucleophilic attack of the motif I Asp on the phosphorus of the substrate, resulting in the formation of a phosphoenzyme intermediate. In HAD-like phosphohydrolases, the metal cofactor (usually Mg 2ϩ ) is involved in the coordination of the nucleophilic side-chain carboxylate of catalytic Asp and the phosphoryl group of the substrate (36,37).…”
Section: Screening Of Purified Proteins For Phosphatase Activity-mentioning
confidence: 99%
“…Earlier work showed that substrate-recognition elements and chemical-catalysis elements are separately located (4)(5)(6)(7)(8)(9). Specifically, substrate recognition is delegated to residues located outside of the core domain active site cleft, whereas phosphoryl transfer is mediated by residues located deep inside this cleft.…”
mentioning
confidence: 99%